Reasons for refusing to donate organs reported by relatives of individuals with brain death - Camatta, Jana Aparecida Paccielli; Berti, Heloisa Wey; Ayres, Jairo Aparecido; Tonete, Vera Lúcia Pamplona (Brazilian Journal of Transplantation, 2011)
Purpose: Study aiming to understand the reasons for the refusal to donate organs by relatives of potential donors living in the Mid-Western region of the São Paulo state. Method: Qualitative study performed after data collection by the Organ Procurement Organization (OPO) Di- vision of a reference hospital in the region. Relatives were contacted to participate in a semi-structured interview, and after the subjects in the study were characterized, four guiding questions were presented; their respective answers were recorded to be transcribed later. The Analysis of Content method proposed by Bardin was used to organize the speeches. Results: From 2006 to 2008, 30 (35.3%) families contacted by OPO have refused to agree with the organ donation. From that universe, 16 family members were interviewed. Data was systematized in three major themes: The experience of being informed on a family member’s brain death, decision concerning to the organ donation and aspects that would facilitate the decision to agree with the organ donation. Conclusion: the identification of reasons for the refusal and the suggestions presented has provided subsidies to improve the organ donation for transplantation process.